2007
DOI: 10.1111/j.1469-7998.2007.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Echolocation calls produced by Kuhl's pipistrelles in different flight situations

Abstract: Flexibility in the echolocation call structure of bats can improve their performances, because, in some situations, some signal designs are better than others. Hence, at least some bats should adjust their echolocation calls according to the setting in which they are operating but also to the specific task at hand, that is their behavioral intention. We studied variation in the echolocation calls of Pipistrellus kuhlii emitted during four flight situations that were similar in setting but differed in behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
0
21
0
3
Order By: Relevance
“…; Berger‐Tal et al. ). However, this potential problem has not been investigated empirically by, for example, testing a model developed in one region on calls from another region.…”
Section: Introductionmentioning
confidence: 98%
“…; Berger‐Tal et al. ). However, this potential problem has not been investigated empirically by, for example, testing a model developed in one region on calls from another region.…”
Section: Introductionmentioning
confidence: 98%
“…The search phase echolocation calls of these three species showed that they share similar call structure in the same kind of cluttered backgrounds, as is the case for other European congeneric species (Ahlén, 1981;Ahlén and Baagøe, 1999;Parsons and Jones, 2000;Schnitzler and Kalko, 2001;Russo and Jones, 2002;Obrist et al, 2004). Pipi strellus maderensis was the species that echolocated with higher start frequency, peak frequency and end frequency, being unambiguously identifiable and distinct from The frequency values for Pipistrellus maderensis are remarkably higher than the values reported to P. kuhlii (Schnitzler et al, 1987;Russo and Jones, 2002;Obrist et al, 2004;Davy et al, 2007;Berger-Tal et al, 2008). In fact, echolocation of P. maderensis revealed higher similarity to P. pipistrellus (Russo and Jones, 2002) than to its ancestral P. kuhlii (Pestano et al, 2003), probably due to the smaller size [forearm length (FA), in mm = 29.5-34.0] of Madeiran P. maderensis (authors' unpublished data) and P. pipistrellus ) in relation to the larger (FA = 30.3-37.1 mm) P. kuhlii (Dietz and von Hel versen, 2004).…”
Section: Discussionmentioning
confidence: 49%
“…However, the echolocation calls are notably more divergent, with P. kuhlii documented to echolocate at a peak frequency between 35 and 46.2 kHz (Schnitzler et al, 1987;Russo and Jones, 2002;Obrist et al, 2004;Davy et al, 2007;Berger-Tal et al, 2008), while P. maderensis echolocates with a peak frequency between 41,3 and 51,7 kHz (herein).…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, from a biological perspective the calls in the vocal repertoire of a species are expected to vary and, thus, the results of a DFA must not be considered meaningless. To reduce the likelihood of misleading classification of the calls because of pseudoreplication (Kazial et al 2001;Berger-Tal et al 2008), we only used three physical features common to all call types in the analysis (i.e. CD, FME, HF).…”
Section: Discussionmentioning
confidence: 99%